Okul öncesi çocuklar için psikolojik dayanıklılık programının 5 yaş çocuklarının sosyal becerlerine ve problem davranışına etkisi - Ünsal, Fatma Özge (My University, 2016)
Bu araştırmada Okul Öncesi Çocuklar İçin Psikolojik Dayanıklılık PDP)’nın 5 yaş çocuklarının sosyal becerilerine ve problem davranışına etkililiğinin belirlenmesi amaçlanmıştır. OÇPDP Baum ve Anchor tarafından 2007 yılında geliştirilen Okul Öncesi Çocuklar için Psikolojik Dayanıklılığın Yapılandırılması ndan Türkçe’ye uyarlanmıştır Araştrırmada veri toplama araçları olarak Avcıoğlu (2007) tarafından geliştirilen “Sosyal Becerileri Değerlendirme Ölçeği, Merril (1994) tarafından geliştirilen Özbey (2009)’da Türkçeye uyarlanan “Anaokulu ve Anasınıfı Davranış Ölçeği Problem Davranışlar Alt Ölçeği” ve araştırmacı tarafından geliştirilen “Kişisel Bilgi Formu” kullanılmıştır. Çalışma grubunu 2014-2015 Eğitim-Öğretim yılı ikinci yarıyılında Marmara Üniversitesi Prof. Dr. Ayla Oktay Okul Öncesi Eğitim Uygulama Birimi’nde eğitim gören 9’u kontrol, 9’u deney 18 çocuk; Semiha Şakir Çocuk Yuvası’nda eğitim gören 12’si kontrol, 11’i deney 23 çocuk; Münevver Şefik Fergar İlkokulu Anasınıfı’nda eğitim gören 10’u kontrol, 16’sı deney 26; olmak üzere 5 yaş grubunda toplam 67 çocuk oluşturmaktadır. Araştırmada deney ve kontrol gruplarının öntestleri çocukların her biri programa başlamadan önce öğretmenler tarafından uygulanmıştır. Okul Öncesi Çocuklar İçin Psikolojik Dayanıklılık PDP) araştırmacının kendisi tarafından 12 hafta süresince haftada iki gün deney grubuna günlük program içerisinde 30 dakika süre ile uygulanmıştır. Kontrol grubu çocukları herhangi bir eğitim almamıştır. Program sonunda ölçekler deney ve kontrol gruplarına tekrar uygulanarak alınan sonuçlar karşılaştırılmıştır. Elde edilen bulgular sonucunda deney ve kontrol grupları arasında istatistiksel olarak anlamlı bir farklılık bulunmuştur. Bu bulgular deney grubunda OÇPDP’ına dahil edilen çocukların herhangi bir özel eğitim almayan çocuklara oranla daha yüksek puanlar aldığını göstermiştir. Bir başka deyişle deney grubundaki çocukların kendini sözel olarak ifade edebilme gibi sosyal becerilerinin arttığı, dışa yönelim, içe yönelim gibi problem davranışlarının azaldığı gözlemlenmiştir. Sonuç olarak Okul Öncesi Çocuklar İçin Psikolojik Dayanıklılık PDP) çocukların problem davranışları ve sosyal becerileri üzerinde etkili olduğu bulunmuştur.

The aim of the study is to find out the effects of the “Resilience Program for Preschool Children” (RPPC) on 5-year-old children’s social skills and behavioral problems. The RPPC was adapted from Building Resilience in Preschool Children written by Baum ve Anchor in 2005. “Social Skills Evaluation Scale (SSES)” developed by Avcıoğlu (2007), “Preschool and Kindergarten Behavior Scale Problem Behaviours Subscale” (PKBS-2) developed by Merril in 1994 and adapted in Turkish by Ozbey in 2009, and “Personal Information Form” (PIF) developed by the researcher were employed data collection tools. These tools were applied to 67 5-year-old children in total at second semester of 2014-2015 academic year, which comprises of 18 children (9 in control and 9 in experimental group) who take education at Marmara University Prof. Dr.Ayla Oktay Preschool Education Center; 23 children (12 in control and 11 in experimental group) who take education at Semiha Şakir Child Care Center; and 26 children (10 in control and 16 in experimental group) who take education at Münevver Şefik Fergar Primary School. Pre-test was applied to each child in both control and experimental group one-to-one by class teacher before implementation of the program. “RPPC” was implemented to children in experimental group for 12 weeks in total, as two days in a week and an activity lasted 30 minutes in a day by reseacher. Not any program was implemented to children in control group. They continued to their standard education program. Post-test was applied to both control and experimental group right after implementation of the program. A statistically significant difference was noted between the experimental and control group pre-test scores (p<0,05). This finding shows that the experimental children who underwent the RPPC had meaningfully higher scores than the control children who did not receive special training. A statistically meaningful difference was also observed between the experimental and control group children’s mean post-test scores adjusted according to mean overall scale pretest scores (p<0,05). In sum, it was seen that the experimental group children who took special training sessions received meaningfully higher scores than the control children who did not undergo any special education, and that the experimental group children possessed more social skills and less problem behaviors than the control group children (p>0,05). In other words, as a result of applied “RPPC”, the social skills such as interpersonal skills , expressing him or herself verbally etc. of the children in the experimental group was observed increased and the behavioral problems such as externalizing, internalizing are decreased. As a result it was found that “RPPC” was effective on 5-year-old children’s social skills and behavioral problems.
Keywords: Eğitim ve öğretim (İlk); Türkiye